Do network externalities and perceived gratifications boost WeChat continued use? Combining perspectives of network externalities and uses and gratifications - Hua Pang; Yuxin Qiao; Yanran Li; Lei Wang (Acta Psychologica)
Rapid burgeoning of mobile social media has become the primary channel by which individuals construct interpersonal networks and contact with each other recently. The primary objectives of this study are to explore how and whether network externalities would enhance WeChat users' distinct types of perceived gratifications, and how such perception of gratifications subsequently impacts their attitudes and continuous usage behavior. This article utilized a structured web-based survey questionnaire to conduct empirical research, and gathered and analyzed data of 788 WeChat users by structural equation modeling (SEM) approach. Perceived gratifications are categorized into three dimensions: hedonic gratifications, social gratifications, and utilitarian gratifications. Obtained outcomes reveal that both referent network size and perceived complementarity are positively and significantly associated with all three dimensions of perceived gratifications. Additionally, hedonic gratifications, social gratifications, and utilitarian gratifications are positively related to users' attitudes toward WeChat, which, in turn, are significantly correlated with their continuous usage behavior. These findings contribute to the growing body of literature on WeChat user behavior, offering novel theoretical insights for academics and practical implications for mobile social media operators.